A sustainable synthesis alternative for IL-derived N-doped carbons: Bio-based-imidazolium compounds. (November 2015) - Yang, Seung Jae; Rothe, Regina; Kirchhecker, Sarah; Esposito, Davide; Antonietti, Markus; Fechler, Nina
Abstract: Herein we report a facile and scalable synthesis of highly nitrogen-doped porous carbon materials with tunable morphology. Bio-based imidazolium derivatives made from natural amino acids and dioxo-derivatives are employed as precursors, exhibiting an analogous behavior during carbonization to classical ionic liquids. Utilization of systematically controlled salt templating methods yields nitrogen-doped carbon materials with high surface areas of up to 2650 m 2 g −1 and morphology-engineered structures such as monolithic or highly extended, sheet-like carbons. We believe that the presented approach represents an alternative and sustainable platform towards the rational design of carbon materials possessing controlled nanoporosity and functionality.